Noise and Vibration Analysis of Power Tillers during Field Operations - Verma, Ajay; Guru, P. K.; Naik, R. K. (International Journal of Bio-resource and Stress Management, 2023)
Every day, millions of agriculture workers were exposed to noise and vibration at work and all the risks of it can entail. This paper examines the noise and vibration characteristics of popularly and most commonly used power tillers having power rating of 11 kW, 9.5 kW and 4.4 kW. Data were collected at four levels of engine speeds for stationary condition of power tiller and two operation modes for tillage and puddling operations. With the increase in engine rpm from ¼ to full of power tillers, noise and vibration magnitude was increased and the allowed exposure was reduced from 7.62 h to 2.48 h for PT-I and 9.83 h to 3.14 h for PT-II and 5.76 h to 2.21 h for PT-III during puddling operation. The SPL of the power tillers under the study was more than the permissible limit of sound level for 8-hour duration/day as recommended by ISO and hence require suitable measures to protect the operator and workers around these power tillers against excessive sound. All three power tillers showed the maximum magnitude of vibration at handle which directly interacts with the body of operator.